2012
DOI: 10.1080/02699931.2011.602047
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the determinants of the graded structure of vocal emotion expressions

Abstract: We examined what determines the typicality, or graded structure, of vocal emotion expressions. Separate groups of judges rated acted and spontaneous expressions of anger, fear, and joy with regard to their typicality and three main determinants of the graded structure of categories: category members' similarity to the central tendency of their category (CT); category members' frequency of instantiation, i.e., how often they are encountered as category members (FI); and category members' similarity to ideals as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
1
21
2
Order By: Relevance
“…For the other three categories, acting does not necessarily appear to be connected with a more exaggerated expression, which is contrary to previous results (Barkhuysen et al, 2007; Laukka et al, 2012). According to our results, play-acted expressions do not represent a socially learned code (Matsumoto et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For the other three categories, acting does not necessarily appear to be connected with a more exaggerated expression, which is contrary to previous results (Barkhuysen et al, 2007; Laukka et al, 2012). According to our results, play-acted expressions do not represent a socially learned code (Matsumoto et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Though actors spend many years perfecting the authenticity and clarity of their portrayals of human behavior and emotions (Goldstein and Bloom, 2011), acted emotional expressions may still be more stereotyped and more intense than spontaneous expressions (Wilting et al, 2006; Laukka et al, 2012, but, see Jürgens et al, 2011; Scherer, 2013), and are thought to be more strongly bound by social codes (Hunt, 1941; Matsumoto et al, 2009). In addition, preselected, stereotypical expressions might conceal possible effects of response biases in cross-culture studies due to their clear and unmistakable expression patterns (Wagner, 1993; Elfenbein et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The use of a forced-choice format has also been criticized on the grounds that it may lead to inflated recognition rates by enabling judges to use informed guessing strategies to a certain extent (e.g., Russell, 1994). Finally, we used portrayed rather than spontaneous vocalizations, whereas some previous studies have reported that acted expressions may be more prototypical and intense than spontaneous expressions (e.g., Laukka et al, 2012). We are addressing the question of a possible in-group advantage in ongoing cross-cultural judgment studies, and would welcome future studies that consider effects of the format of the judgment task and type of expressive stimuli on cross-cultural emotion decoding (e.g., Jürgens et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In an examination of prototypicality, Laukka and colleagues tested the perception of segments of speech inflected with anger, fear, or joy (Laukka, Audibert, & Aubergé, 2012). Their results lend some support to the notion that expressions that are more prototypical are better recognised, but whether this relationship applies to nonverbal vocalisations is not yet clear.…”
Section: The Current Studymentioning
confidence: 99%